Effectiveness of Implementing Green Financing as an Alternative Sustainable Financing - Virginia Mandasari; Alfiandi Imam Mawardi; Nanik Hariyana (Nusantara Science and Technology Proceedings, 2023)
Many businesses in the past prioritized high profits over the detrimental effects on the economy, environment, and society. The performance of businesses that do not emphasize adverse effects on the economy, environment, and society is unpopular with the general public. Finally, businesses are beginning to consider sustainability-related challenges. The goal of sustainability is to satisfy current needs without jeopardizing the ability of future generations to satisfy their own. Economic, environmental, and social factors make up the three pillars that make up the notion of sustainability. Through sustainability reports, businesses can inform the public about their sustainability performance. The Global Reporting Initiatives (GRI) are the standards used to produce sustainability reports. According to the Financial Services Authority's (OJK) roadmap for sustainable finance, banking also helps to promote sustainability. The activities are carried out by putting green financial products into practice. Green financing products are those that take environmental considerations into account. The Green Finance concept is based on a balance of three points of view (Triple Bottom Line), namely Profit, People, and Planet, which emphasizes not only optimizing economic factors but also paying attention to sustainability and preserving environmental factors. The public also demands that companies follow the Green Finance concept to achieve environmental improvements which must go hand in hand with economic development.